2013
DOI: 10.1017/s1368980012005575
|View full text |Cite
|
Sign up to set email alerts
|

Meeting school food standards – students’ food choice and free school meals

Abstract: Objective: To examine students' school food choice in relation to school food standards and entitlement to free school meals (FSM). Design: Cross-sectional analysis of students' school food choices. Setting: Two large secondary schools in Yorkshire, England. Subjects: Students (n 2660) aged 11-18 years. Results: Sandwiches and pizza were the most popular main food items: 40?4 % and 31?2 %, respectively, in School A; 48?3 % and 27?3 %, respectively, in School B. More nutritionally valuable 'dishes of the day' a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Previous research has shown how food choice can be changed by the position of foods, e.g., first in the line of foods available, or near the tills [ 53 , 54 ]. Similarly, adolescents’ predisposition for “grab-and-go” foods [ 7 ] can be applied to promote the uptake of plant-based foods, e.g., in providing meals in a portable disposable bowl. In this way, it is proposed that plant-based foods are more accessible to adolescents and likely to become part of their daily food habits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown how food choice can be changed by the position of foods, e.g., first in the line of foods available, or near the tills [ 53 , 54 ]. Similarly, adolescents’ predisposition for “grab-and-go” foods [ 7 ] can be applied to promote the uptake of plant-based foods, e.g., in providing meals in a portable disposable bowl. In this way, it is proposed that plant-based foods are more accessible to adolescents and likely to become part of their daily food habits.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of British 15-year-olds do not meet the recommended five portions of fruit and vegetables every day; further, 64% do not eat fruit daily and 63% do not eat vegetables daily [ 5 ]. Adolescents’ diet is also generally marked with poor food choice, including a high proportion of nutrient-poor and fast foods [ 6 , 7 , 8 ]. The implication of this on public health is well-documented [ 9 , 10 , 11 ]; and the high burden of disease due to unhealthy dietary patterns has been acknowledged by World Health Organisation European Member States, with particular concern for childhood obesity and overweight [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The data from the cashless system provided genuine insights into students’ food choice, and enabled the impact of the intervention to be accurately evaluated. The power and value of using such data to examine students’ dietary patterns has been shown previously [ 3 , 20 ], and this study adds to the literature, in particular with respect to monitoring a change accompanying a nutrition intervention.…”
Section: Discussionmentioning
confidence: 71%
“…Adolescents’ diet in the UK is high in saturated fat and sugar, along with low fruit and vegetable consumption [ 1 ]; generally marked by poor food choice, a propensity for fast or grab-and-go foods has been illustrated in previous studies [ 2 , 3 , 4 ]. These choices, typified by low intake of plant-based foods, are mirrored in school canteens, where students commonly bypass freshly prepared nutrient rich meals [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study have examined students food choices in relation to food standards and free foods provided by the school, which is another important measurement that indicates how the behavior is related to school meal options. In that study, sandwiches, pizza and desserts, were the most chosen items [36], which are rich in carbohydrates and fats. In agreement with our study, a cross sectional study was carried in the year 2013 to assess school meals of preschools, and results showed that mean intake of calories is 339 kcal, which is similar to the current study meals energy level (420kcal).…”
Section: Discussionmentioning
confidence: 99%